2017
DOI: 10.20420/rlfe.2016.327
|View full text |Cite
|
Sign up to set email alerts
|

Form-Focused Data-Driven Learning for Grammar Development in ESP Contexts

Abstract: The use of corpus-informed language in English for Specific Purposes (ESP) / English for Academic Purposes (EAP) teaching has considerably grown over the past two decades, especially due to the proliferation of course book material based on corpora. However, in terms of learning approaches to grammatical items, much less has been published commercially to train teachers in the use of corpora and their exploitation. DDL (Data-Driven Learning) techniques are still something to foster and publicize for ESP scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Additionally, Bandar and Gorjian (2017) proved that combining FonF and focus on meaning strategies enhanced Iranian EFL senior high school male students' acquisition of Wh-questions. In Spain, Fuentes (2017) found that integrating FonF instruction with DDL fostered EFL business administration and tourism majors' acquisition of grammar. Saadi and Saeidi (2018), also, found that typographical IE and the output task of producing sentences fostered Iranian EFL intermediate level adult male learners' acquisition of conditional sentences, the passive voice and the past perfect tense.…”
Section: Advantages Of Fonf Implementation In Esl/ Efl Classroomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Bandar and Gorjian (2017) proved that combining FonF and focus on meaning strategies enhanced Iranian EFL senior high school male students' acquisition of Wh-questions. In Spain, Fuentes (2017) found that integrating FonF instruction with DDL fostered EFL business administration and tourism majors' acquisition of grammar. Saadi and Saeidi (2018), also, found that typographical IE and the output task of producing sentences fostered Iranian EFL intermediate level adult male learners' acquisition of conditional sentences, the passive voice and the past perfect tense.…”
Section: Advantages Of Fonf Implementation In Esl/ Efl Classroomsmentioning
confidence: 99%
“…From a pedagogical point of view, FonF was originally introduced as an effective instructional approach to foster grammatical patterns acquisition among ESL/ EFL learners while ensuring meaningful authentic communication of ideas and emotions (Saeidi & Chong, 2003;Mohamed, 2006;Othman & Ismail, 2008). Based on research findings, FonF was found effective in promoting grammar skills among varied ESL/ EFL learners in different educational settings as in the studies of Saeidi and Chong (2003), Mohamed (2006), Bernet, Kelly, Aldersley, Schmitz, Khalsa, Panara and Keenan (2007), Fuentes (2017), Alqahtani (2019) as well as Xu and Li (2022).…”
Section: Introductionmentioning
confidence: 99%